Online modeling of virtual energy storage for inverter air conditioning clusters in CDL-based demand response - Lingling Zhu; Juhua Hong; Siyu Yang; Zhenda Hu; Yunfei Shao; Chengxin Wu; Guangyu He (Energy Reports, 2023)
In recent years, the accelerated penetration of renewable energy hinders the flexible adjustment of power systems. Customer directrix load (CDL)-based demand response (DR) unlocks the potential flexibilities of inverter air conditioning in industrial or commercial parks and promotes the integration of renewable energy. Although there have been extended researches regarding the inverter air conditioning, most of the them belongs to the offline method, which does not consider the time-varying nature of the air conditioning model parameters. Therefore, this paper proposes the CDL-based DR scheme for the cluster of inverter air conditionings through the online virtual energy storage modeling. First, we propose the online virtual energy storage modeling method leveraging the outputs of online identification of the second-order equivalent thermal parameters (ETP) model. Then, the virtual energy storage characteristics of inverter air conditioners were analyzed by the time decoupling charge and discharge control method. Furthermore, we propose an intraday rolling DR optimization model for the cluster of inverter air conditionings, which overcomes the adversarial factors caused by temporal variability of ETP parameters. We utilize variable frequency air conditioning cluster to participate in the park DR based on customer directrix load (CDL). The case study corroborates the effectiveness of the proposed online virtual energy storage modeling.